Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan Kejadian Hipertensi Di Wilayah Kerja Puskesmas Martapura Tahun 2017 - Siska Dhewi (HB PRESS, 2017)
MMR (Maternal Mortality Rate) in Indonesia, one of which is caused by hypertension in pregnancy. Based on data obtained in Martapura Public Health Center in 2016 was recorded in 1499 among pregnant women there who had hypertension as many as 40 people. The purpose of this study is to investigate the correlation between knowledge and attitude of pregnant women against hypertension in pregnancy. This study uses an analytical method, data collection using questionnaires, and sampling purposive sampling. Results showed that respondents have a good knowledge of hypertension were 69 respondents (77,5%), while the positive attitude of respondents who behave as much as 64 respondents (71,9%). From the statistical results using Chi Square test with α = 0.05 p value = 0.036, this means there is significant correlation between knowledge of the incidence of hypertension in pregnant women. The results using Chi Square statistic with α = 0.05 p value = 0,001, this means there is significant correlation between attitude with hypertension in pregnant women. Based on the results, for health personnel in order to improve services to pregnant women so as to reduce the risk of hypertension